Vibegron for the Treatment of Patients with Dry and Wet Overactive Bladder: A Subgroup Analysis from the EMPOWUR Trial - David Staskin; Jeffrey Frankel; Susann Varano; Michael Kennelly; Diane K. Newman; Matt T. Rosenberg; Denise D. Shortino; Rachael A. Jankowich; Paul N. Mudd Jr (International Journal of Clinical Practice)
Background. Overactive bladder (OAB) is characterized by urgency and frequency with (OAB wet) or without (OAB dry) urge urinary incontinence (UUI). In the phase 3 EMPOWUR trial, vibegron—a selective β3-adrenergic receptor agonist for the treatment of OAB—significantly improved daily number of urgency episodes and micturitions vs. placebo (P < 0.01). These post hoc analyses aimed to compare the efficacy of vibegron vs. placebo in OAB dry and wet populations. Methods. Patients were randomly assigned 5:5:4 to receive once-daily vibegron 75 mg, placebo, or tolterodine 4 mg extended release, respectively, for 12 weeks. Baseline criteria for OAB dry included an average of ≥8 micturitions, ≥3 urgency episodes, and <1 UUI episode per diary day and for OAB wet included an average of ≥8 micturitions and ≥1 UUI episode per diary day. Change from baseline in mean daily number of urgency episodes and micturitions was assessed in both populations. Results. Of the 1463 patients included in the full analysis set, 336 (23%) had OAB dry (vibegron, N = 123; placebo, N = 115; and tolterodine, N = 98), and 1127 (77%) had OAB wet (vibegron, N = 403; placebo, N = 405; and tolterodine, N = 319). Vibegron was associated with significant reductions (95% CIs of the least squares mean differences [LSMD] does not include 0) from baseline at week 12 vs. placebo in mean daily urgency episodes for the dry (LSMD [95% CI], ‒1.0 [‒2.0, ‒0.1]) and wet (‒0.6 [‒1.0, ‒0.1]) populations. Vibegron was associated with significant reductions from baseline at week 12 vs. placebo in mean daily micturitions for the dry (LSMD [95% CI], ‒0.8 [‒1.5, ‒ 0.1]) and wet (‒0.5 [‒0.8, ‒0.1]) populations. There were no significant differences in either outcome between tolterodine and placebo for either the dry or wet populations in this study. Conclusions. In this subgroup analysis from the EMPOWUR trial, vibegron was associated with significant reductions compared with placebo in urgency episodes and micturitions in both the OAB dry and wet populations, suggesting that vibegron is similarly efficacious for these endpoints in patients with and without UUI. This trial is registered with NCT03492281.